Evolution of the Crop Rhizosphere: Impact of Domestication on Root Exudates in Tetraploid Wheat (Triticum turgidum L.) - Iannucci, Anna; Fragasso, Mariagiovanna; Beleggia, Romina; Nigro, Franca; Papa, Roberto (Frontiers in Plant Science, 2017)
Domestication has induced major genetic changes in crop plants to satisfy human needs and as a consequence of adaptation to agroecosystems. This adaptation might have affected root exudate composition, which can influence the interactions in the rhizosphere. Here, using two different soil types (sand, soil), we provide an original example of the impact of domestication and crop evolution on root exudate composition through metabolite profiling of root exudates for a panel of 10 wheat genotypes that correspond to the key steps in domestication of tetraploid wheat (wild emmer, emmer, durum wheat). Our data show that soil type can dramatically affect the composition of root exudates in the rhizosphere. Moreover, the composition of the rhizosphere metabolites is associated with differences among the genotypes of the wheat domestication groups, as seen by the high heritability of some of the metabolites. Overall, we show that domestication and breeding have had major effects on root exudates in the rhizosphere, which suggests the adaptive nature of these changes.